Influence of body configuration on kinetics and multijoint control strategies sprinters use during the first step out of blocks - Stewart, H. E.; Wilcox, R. R.; McNitt-Gray, J. L. (Journal of Applied Biomechanics, 2026)
Sprinters need to generate horizontal impulse quickly in the first step out of the blocks to accelerate the body toward the finish line. The purpose of this study was to determine how body configuration at initial foot contact was correlated to ground reaction force measures and multijoint control during the first step out of the blocks by highly trained to world-class sprinters. Measurements of ground reaction forces and segment kinematics during sprint starts performed during a training session revealed that positioning the foot further behind the center of mass at initial contact significantly correlated with shorter contact times, greater average horizontal forces, and increased net joint moment impulse on the knee during the impact phase. Increases in average horizontal forces were significantly correlated with smaller magnitudes of shank angular velocity during the impact phase and shorter times to peak thigh angular velocity during the postimpact phase. We also used kinetic and kinematic data to provide feedback regarding an athlete`s mechanics to coaches for use within a training session on the track.